2004
DOI: 10.1177/1099800404264846
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Correlates of Fatigue in HIV Disease

Abstract: Fatigue is a frequent symptom reported by persons living with HIV disease and one that affects all aspects of quality of life. To improve quality of care of persons with HIV disease, it is important to address all factors that contribute to fatigue. The purpose of this study was to determine the associations of physiological, psychological, and sociological factors with fatigue in an HIV-infected population. With Piper's integrated fatigue model guiding selection, factors examined in this study were hemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
52
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 76 publications
11
52
3
Order By: Relevance
“…81% were on ART with a mean current CD4 cell count of 579 -284 cells/mm 3 . The majority of the patients (81%) had undetectable viral load; 52 (27%) participants reported loud snoring, and 47 (24%) reported witnessed apneas.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…81% were on ART with a mean current CD4 cell count of 579 -284 cells/mm 3 . The majority of the patients (81%) had undetectable viral load; 52 (27%) participants reported loud snoring, and 47 (24%) reported witnessed apneas.…”
Section: Resultsmentioning
confidence: 99%
“…F atigue is one of the most common self-reported and provider-identified symptoms in persons living with HIV/AIDS (PLWH) 1 with a prevalence ranging from 60% in HIV infection 2,3 to 85% among those with AIDS. 3 Several predictors of fatigue are common in this population, including systemic inflammation, anxiety, depression, chronic pain, aging, medical co-morbidities, and sleep disturbances.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[26] Therefore, it is important for physicians to address this problem using the available treatment options. [27] The second most prevalent problem was that of lack of energy in the body, or fatigue (96.4%). Other studies have also reported it to be one of the common problems.…”
Section: Discussionmentioning
confidence: 99%